1989
DOI: 10.1016/0039-6028(89)90083-6
|View full text |Cite
|
Sign up to set email alerts
|

Forward focusing of Auger and Kikuchi electrons for surface structure determination: Ni(100) and oxidized Mg(0001)

Abstract: Angular profiles of "Kikuchi" and Auger electrons were measured and interpreted for a clean Ni(100) surface and a slightly oxidized Mg(OOOI) surface. Theoretical analysis of the data using forward focusing of the medium-energy electrons (500-1500 e V) shows that both Kikuchi and Auger electrons can be well represented as s-waves emitted from atomic sites. The Auger electron data are used to analyze the structure of slightly oxidized Mg(OOOI), yielding oxygen atom positions in the octahedral interstitial sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…As the energy is increased, the intensities of these beams first pass a succession of maxima and minima and then gradually fade away. When the diffracted beams disappear, several experiments have shown that the electrons are reflected in all directions with broad intensity maxima at directions that can be associated with crystal chains of atoms [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] . Because of this drastic change in the angular pattern, a LEED experiment extended into this energy region is often referred to as medium-energy electron diffraction ͑MEED͒.…”
Section: Introductionmentioning
confidence: 99%
“…As the energy is increased, the intensities of these beams first pass a succession of maxima and minima and then gradually fade away. When the diffracted beams disappear, several experiments have shown that the electrons are reflected in all directions with broad intensity maxima at directions that can be associated with crystal chains of atoms [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] . Because of this drastic change in the angular pattern, a LEED experiment extended into this energy region is often referred to as medium-energy electron diffraction ͑MEED͒.…”
Section: Introductionmentioning
confidence: 99%
“…Very surprisingly, when the diffracted beams disappear the angular pattern becomes similar to those measured in XPD and AED experiments. [5][6][7][8][9][10][11][12][13][14][15][16] Because of this new characteristic, a LEED experiment extended into this energy region is often referred to as medium-energy electron diffraction ͑MEED͒. The high counting rates in MEED and the direct relation of the structures in the angular pattern with the real lattice have been exploited in different crystallographic studies.…”
Section: Introductionmentioning
confidence: 99%
“…The high counting rates in MEED and the direct relation of the structures in the angular pattern with the real lattice have been exploited in different crystallographic studies. 9,11,12,15 However, in spite of some successful applications, the poor understanding of the origin of the XPD/AED-like structures has hindered the use of MEED as a crystallographic tool beyond a qualitative level. It is generally assumed that the electron undergoes an inelastic collision at an atomic site and that thereafter it evolves as having been emitted from that site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our survey, we included the adsorption sites suggested by earlier studies 6,11,12 along with a number of other positions above and below the surface. 18 Of these, the stable sites are sketched in Fig.…”
mentioning
confidence: 99%